Honed Leadership Skills: An Experience Based Approach - Ryan Restu P; M. Isa Anshori; Moh.Marwasi; Siti Masrifah; Desika Livania (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Leadership is a vital skill in a variety of life contexts, including education, business, and society. This scientific article presents a comprehensive review of how to hone leadership skills through an experience-based approach. The research method used is a qualitative approach. The data used is data sourced from literature review. We explain key concepts in leadership, outline experience-based approaches, and identify the benefits and challenges associated with these approaches. Additionally, we offer practical strategies for implementing experience-based approaches in educational and leadership development contexts. This scientific article aims to provide a deeper understanding of how direct experience can be a strong foundation in developing effective leadership skills.